ACADEMIC INTEGRITY SUPPORT SYSTEM FOR UKRAINIAN UNIVERSITIES - Sherstjuk, V. G.; Zharikova, M. V. (Science and Transport Progress, 2017)
Purpose. Developing the methodology for providing academic integrity in the university. The methodology is based on Web-oriented academic integrity support system, developed by the authors, which enters into the information system of learning process control. Academic integrity support system is aimed at maintaining academic integrity as a basic institutional value, which will help to reduce corruption, plagiarism and other types of academic dishonesty. Methodology. The methodology of problem to solve is based on the development of the information system of education process control with the integral elements of quality control. The information subsystem of academic integrity support is its basic part. Findings. The proposed information system allows us to fulfill the following levels: educational process monitoring; audit of internal processes, which is necessary for developing the effective quality control system; assessment of achievements of educational process participants; formalization of the interaction of educational process participants. The system is aimed at the development of new academic society based on the following principles: open access to the information, at which the access of wide audience to the information provides participation, forming the sense of responsibility and social control; transparency of the information, by which its relevance, quality, reliability are meant; responsibility of all members of educational process; measurability, at which any action in educational process should be measured; detail of describing the actions, results and processes; support, which is meant by automatic tools of the realization of the principles of open access to the information, transparency of the information, responsibility of all participants of educational process, measurability, detail, support. The practical realization of information system is based on the development of a common repository of university information. The repository should be organized as a hypercube having abundance of dimensions, for example by students, teachers, courses, rooms, educational programs and plans. Originality. The new four-level concept of the information system of academic integrity support is first proposed. Practical value. The proposed system allows increasing dishonesty in academic society and gives rise to the integration of Ukrainian universities into the Europe. The proposed ideas will be represented in the pilot project of information system of learning process control in Kherson National Technical University.